Education Financing Management in Improving the Quality of Financial Management Accountability - Heriyanto Heriyanto; Iim Wasliman; Waska Warta; Yoyok Prasetyo (International Journal of Nusantara Islam, 2026)
This study aims to analyze education financing management in improving the quality of financial governance accountability in private higher education institutions, using Bandung Islamic University (UNISBA) as a case study. The key concepts examined include education financing management, financial accountability, transparency, and university governance. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, document analysis, and data triangulation. The scope of the study focuses on the processes of planning, organizing, implementing, supervising, and ensuring accountability of education financing at UNISBA. The findings reveal that UNISBA has implemented relatively effective education financing management through data-driven budget planning, a well-defined financial organizational structure, disciplined budget implementation, systematic internal supervision, and transparent financial reporting. However, the study also identifies several challenges, including revenue uncertainty, external policy dynamics, and increasing demands for educational quality improvement. The study recommends strengthening internal control systems, optimizing financial information technology, and enhancing human resource capacity as key strategies to improve financial governance accountability in private universities. This study contributes to the literature on education financing management by providing a comprehensive analytical framework that integrates financial planning, implementation, supervision, and accountability within the context of private higher education institutions in Indonesia.